A method for generating virus-free cassava plants to combat viral disease epidemics in Africa - Maruthi, M.N.; Whitfield, E.C.; Otti, G.; Tumwegamire, Silver; Kanju, E.; Legg, James P.; Mkamilo, G.; Kawuki, R.S.; Benesi, I.R.M.; Zacarias, A.; Munga, T.; Mwatuni, F.; et al. (Elsevier, 2019)
Here, we report a method to clean cassava plants from viral infections that cause cassava mosaic and brown streak diseases in Africa. Infected plants of resistant or tolerant varieties from Malawi, Mozambique, Kenya, Tanzania and Uganda were cleaned in the UK using a combination of tissue culture, chemotherapy and thermotherapy. In the first cycle of our virus-indexing procedure, we successfully cleaned 27 of the 31 varieties (87%), and after an additional three cleaning cycles, all plants were virus-free. Virus-free tissue-cultured plants were shipped back to Africa for distribution to farmers. This first cross-boundary effort provides important lessons for mitigating the two-major cassava viral diseases.